Photo-Curable Lacquer Sap Resin Based on Urushiol-Mimicking, Tyrosine-Containing Additive - Park, Jiwon; Jin, Seon-Mi; Mishra, Avnish Kumar; Lim, Jung Ah; Lee, Eunji (American Chemical Society, 2022)
Oriental lacquer sap is attracting considerable attention as a renewable and eco-friendly natural resin with high durability, heat resistance, insulation, insect repellency, and antiseptic and antibacterial properties. However, to ensure excellent coating performance, it is necessary to improve the drying/curing process of lacquer sap with a time-consuming drying time at high humidity [relative humidity (RH), 70-90%] and ambient temperature (20-30 ?). Drawing on an understanding of the polymerization mechanism of urushiol, the main component of the lacquer sap consisted of a water-in-oil (W/O) emulsion, and this study presents an eco-friendly additive that mimics the structure-function of urushiol composed of a polar catechol head group and a nonpolar hydrocarbon tail. A photo-curable lacquer sap was thus developed by adding a tyrosine amino acid-based lipid agent (denoted as Y-ADDA), which allows faster and more effective drying/curing at lower humidity while maintaining the nature-derived properties of lacquer sap. Y-ADDA easily coassembles with urushiol in the W/O emulsion droplets, thereby significantly accelerating the formation of a polymer network along with urushiol during water evaporation leading to fast drying/curing under ultraviolet (UV) light irradiation at low humidity (similar to 50% RH). The UV-cured lacquer sap resins showed higher performance in terms of film processing and physicochemical properties compared with that of the lacquer containing only tyrosine amino acids without aliphatic tail conjugation, N-(9-fluorenylmethoxycarbonyl)-O-tert-butyl-L-tyrosine Fmoc-Tyr(tBu)-OH. Furthermore, the drying and curing times, film morphology, transmittance, hardness, and adhesion strength of the UV-cured lacquer were markedly superior compared to those of shellac, a general eco-friendly fast-drying primer. The study provides useful strategies and insights to promote the industrial application of lacquer sap resins by employing biocompatible nanoagents developed with an understanding of the curing mechanism of natural resins and from the viewpoint of green and sustainable chemistry perspective.